Tuberculosis geoprocessing in the city of Santos – SP between 2006 and 2016 (Research, Society and Development, 2022)
To perform a Tuberculosis Geoprocessing in the city of Santos in the period between 2006 and 2016 in order to identify the regions with the highest number of cases in the city. The present study is characterized as ecological and temporal trend, as it retrospectively evaluated all cases of Tuberculosis in the city of Santos between 2006 and 2016. The requested data were provided by the Epidemiological Surveillance Center of the state of São Paulo, being provided by CVE-SP. The database consisted of 4533 cases for the city of Santos Results: The highest concentration of cases occurred in the Northwest of Santos, comprising the districts Rádio Clube, Chico de Paula and Bom Retreat, a port region in the neighborhood of Paquetá and Vila Nova. A third area of ​​concentration of cases is located in the region comprising Monte Serrat, Vila Progresso and Saboó. neighborhoods of Paquetá, Vila Matias and Vila Nova (81 cases) and the region made up of the neighborhoods Alemoa, Radio Clube, Bom Retiro and São Jorge (103 cases). These two main regions totaled 184 cases, representing approximately 62% of all cases observed in the city. Three main regions were identified that contributed to most of the cases in the city, namely, the northwest zone, the port region of Paquetá and the region of hills of Nova Cintra and Monte Serrat. Public policies aimed at these three regions can prevent the persistence of the spread of cases between them.